Creation and (Re)presentation of Historical Discourse in Isle of Passion by Laura Restrepo - Daniela Melis (Studies in 20th & 21st Century Literature, 2011)
Published in Colombia in 1989, but neglected until the author’s later distinction, Laura Restrepo’s first novel, Isle of Passion, focuses on historical facts, as well as on the issues that arise when the impact of events is articulated in official discourse. This study—drawing from Walter Mignolo’s idea of decolonial theory—explores how Restrepo’s attempt to rewrite history following “an-other logic, an-other language, an-other thinking” contributes to the decolonization of knowledge, being, community interests, and cultural heritage. The novel’s plot centers on a minor event in international history: the territorial dispute over the island of Clipperton, which was encountered by an English pirate escaping the Spaniards in the 1700’s, claimed by the Mexicans for its geographical proximity, owned (since 1930) by the French, and occasionally disputed by the English and US governments. Writing while personally experiencing the trauma of exile, Restrepo narrates the forgotten story of the Mexican soldiers—deployed with their families to defend the island—as a metaphor of marginalization. Clipperton, therefore, represents not only a geographical, but also a historical entity. This reading of Isle of Passion describes how its creative dis-order recovers a chapter of national history, finally retold by its silenced protagonists.
Keywords: Laura Restrepo; novel; Isle of Passion; Colombian literature; exile; marginalization